A Deformable Nanoplasmonic Membrane Reveals Universal Correlations Between Plasmon Resonance and Surface Enhanced Raman Scattering. (26th March 2014) - Kang, Minhee; Kim, Jae‐Jun; Oh, Young‐Jae; Park, Sang‐Gil; Jeong, Ki‐Hun
<x xml:space="preserve">Abstract</x> A quantitative correlation between plasmon resonance and surface enhanced Raman scattering (SERS) signals is revealed by using a novel active plasmonic method, that is, a deformable nanoplasmonic membrane. A single SERS peak has the maximum gain at the corresponding plasmon resonance wavelength, which has the maximum extinction product of an excitation and the corresponding Raman scattering wavelengths. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>